2015
DOI: 10.1152/ajprenal.00515.2014
|View full text |Cite
|
Sign up to set email alerts
|

Renal nerve stimulation leads to the activation of the Na+/H+exchanger isoform 3 via angiotensin II type I receptor

Abstract: Renal nerve stimulation at a low frequency (below 2 Hz) causes water and sodium reabsorption via α1-adrenoreceptor tubular activation, a process independent of changes in systemic blood pressure, renal blood flow, or glomerular filtration rate. However, the underlying mechanism of the reabsorption of sodium is not fully understood. Since the sympathetic nervous system and intrarenal ANG II appear to act synergistically to mediate the process of sodium reabsorption, we hypothesized that low-frequency acute elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 61 publications
6
37
0
1
Order By: Relevance
“…This associated response may suggest that either UGE or UFR was the primary effect of stimulation, while the other was a secondary response. Previous studies that applied stimulation of renal nerves at low frequencies observed a 25-52% reduction in UFR (Bello-Reuss et al 1976;Pontes et al 2015). Those percentages align with the average reduction of UFR we observed at low frequency stimulation (28% at 2 Hz, 41% at 5 Hz), suggesting that UFR may be the primary response of stimulation at low frequencies.…”
Section: Discussionsupporting
confidence: 89%
“…This associated response may suggest that either UGE or UFR was the primary effect of stimulation, while the other was a secondary response. Previous studies that applied stimulation of renal nerves at low frequencies observed a 25-52% reduction in UFR (Bello-Reuss et al 1976;Pontes et al 2015). Those percentages align with the average reduction of UFR we observed at low frequency stimulation (28% at 2 Hz, 41% at 5 Hz), suggesting that UFR may be the primary response of stimulation at low frequencies.…”
Section: Discussionsupporting
confidence: 89%
“…Another important factor to consider is renal sympathetic nervous system activation secondary to renal injury which prevents retraction of NHE3 out of the microvilli in the face of hypertension and blunts natriuresis. 5, 55, 56 …”
Section: Mediators Of Pressure Natriuresismentioning
confidence: 99%
“…Moreover, these effects were completely blunted by AT 1 receptor blockade prior to low‐frequency RNS (Pontes et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, we have recently found that low‐frequency RNS significantly increases intrarenal, but not systemic, Ang II (Pontes et al . ). These studies further our understanding of the crosstalk between the renal sympathetic nerve and intrarenal Ang II, which influences sodium and water reabsorption.…”
Section: Introductionmentioning
confidence: 97%